Respuesta :
3m -9n = 24
3m -9 (-1)= 24
3m + 9 = 24
- 9 = -9
3m = 15 divide by both side by 3
m = 5
3m -9n = 24
3m -9 (1) = 24
3m -9 = 24
+9 = 9
3m = 33 Divide by both side by 3
m = 11
3m -9n = 24
3m -9(3) = 24
3m -27 = 24
+27 = 27
3m = 51 Divide by both side by 3
m = 17
3m -9 (-1)= 24
3m + 9 = 24
- 9 = -9
3m = 15 divide by both side by 3
m = 5
3m -9n = 24
3m -9 (1) = 24
3m -9 = 24
+9 = 9
3m = 33 Divide by both side by 3
m = 11
3m -9n = 24
3m -9(3) = 24
3m -27 = 24
+27 = 27
3m = 51 Divide by both side by 3
m = 17
Answers:
at n = -1 ............> m = 5
at n = 1 ............> m = 11
at n = 3 ..........> m = 17
Explanation:
The given equation is:
3m - 9n = 24
We want to get the value of m at given values of n.
Therefore, we will simply substitute with the given n in the equation and solve form m as follows:
1- At n = -1:
3m - 9n = 24
3m - 9(-1) = 24
3m + 9 = 24
3m = 24 - 9
3m = 15
m = 5
2- At n = 1:
3m - 9n = 24
3m - 9(1) = 24
3m - 9 = 24
3m = 24 + 9
3m = 33
m = 11
3- At n = 3:
3m - 9n = 24
3m - 9(3) = 24
3m - 27 = 24
3m = 24+ 27
3m = 51
m = 17
Hope this helps :)